Perbaikan metode kerja dengan metode Mynard Operation Sequence Technique (Studi Kasus: CV. Usaha Bersama) - Sudrajat, Andi; Yudisha, Nabila (Program Studi Teknik mesin, Fakultas Teknik, Universitas Al Azhar Medan, 2023)
Since activities require movement, such as moving, lifting, and assembling goods, consequently, work movement analysis is essential for businesses, especially for manufacturing companies that perform many movement activities during the manufacturing process. The way to calculate the amount of work is MOST (Maynard Operation Sequence Time), which is based on a sequence of actions or subactivities. Repetitive motion is the basis of this subactivity. The purpose of this study is to improve the working method with the MOST method with qualitative research methods and observations by concluding the standard time obtained is as follows: standard time 6.853 / minute standard output 0.06127 boats / day. While the time needed to complete one boat is 20 days